The Impact of Psychological Support On Improving The Achievement Of Slow Learner Students - Rachmawati Musslifah, Anniez; Henny Lukitasari, Evelyne; Primasanti, Yunita (Chakra Brahmanda Lentera Institute, 2024)
Background: Collaboration between teachers, parents, and school counselors is essential to provide ongoing psychological support. By engaging a counselor, students can obtain guidance services that help them manage stress, develop study skills, and build confidence. This inclusive and adaptive approach allows every student, both fast and slow learners, to reach their best potential academically and emotionally. This paper aims to explore more about the concept of psychological support for improving the achievement of slow learner students at SMK Negeri 9 Surakarta, Indonesia. Methods: This study uses a qualitative design with a field approach at SMK Negeri 9 Surakarta, collecting data through interviews, observations, and documentation supported by relevant literature and theoretical frameworks. Participants included class X educators. Data analysis employed triangulation, involving data reduction, display, and conclusion drawing to ensure validity and identify key themes. The findings are presented descriptively, addressing the research focus and supported by prior studies. Results: The results of the study show that SMK Negeri 9 Surakarta has compiled a guideline known as